Preclinical Models of Traumatic Brain Injury: Emerging Role of Glutamate in the Pathophysiology of Depression - O’Neil, Darik A.; Nicholas, Melissa A.; Lajud, Naima; Kline, Anthony E.; Bondi, Corina O. (Frontiers in Pharmacology, 2018)
More than 10 million people worldwide incur a traumatic brain injury (TBI) yearly, with two million cases occurring in the United States. TBI survivors exhibit long-lasting cognitive and affective sequelae that are associated with reduced quality of life and work productivity, as well as mental and emotional disturbances. While TBI-related disabilities often manifest physically and conspicuously, TBI has been linked with a “silent epidemic” of psychological disorders, including major depressive disorder (MDD). The prevalence of MDD post-insult has been placed at nearly 50% within the first year. Furthermore, given they are often under-reported when mild, TBIs could be a significant overall cause of MDD in the United States. The emergence of MDD post-TBI may be rooted in widespread disturbances in the modulatory role of glutamate, such that glutamatergic signaling becomes excessive and deleterious to neuronal integrity, as reported in both clinical and preclinical studies. Following this acute glutamatergic storm, regulators of glutamatergic function undergo seismic manipulations, which include, but are not limited to, alterations in glutamatergic subunit composition, release, and reuptake. This review will characterize the glutamatergic functional and signaling changes that emerge and persist following experimental TBI, utilizing evidence from clinical, molecular, and rodent behavioral investigations. Special care will be taken to speculate on how these manipulations may correlate with the development of MDD following injury in the clinic, as well as pharmacotherapies to date. Indisputably, TBI is a significant healthcare issue that warrants discovery and subsequent refinement of therapeutic strategies to improve neurobehavioral recovery and mental health.